Risk Avoidance Behavior on Darknet Marketplaces - Howell, Christian Jordan (Crime & delinquency, 2024)
The current study employs a quasi-experimental design to test the efficacy of situational crime prevention (SCP) in understanding risk avoidance behavior in a darknet environment. Specifically, we deployed a web scraper to extract data from a popular darknet market. We then used these data to assess change in vendors and customers? behavior following the deliverance of a warning message from the market administrator regarding the former market administrator?s intention to scam market participants. In the one-month following the message, vendors posted fewer advertisements and customers spent less and made fewer transactions on the marketplace. These findings expand the scope of SCP and provide evidence for Hutchings and Holt?s notion that darknet markets can be disrupted by means of gossip.